SHOULD THE VIOLATORS OF MANDATORY COVID-19 VACCINATION BE PUNISHED IN INDONESIA?: HUMAN RIGHTS PERSPECTIVE - Zaid Zaid (Diponegoro Law Review, 2023)
This study explores human rights perspectives on Indonesia's mandatory COVID-19 vaccination policy, particularly examining the associated penalties for non-compliance. This research is applying a normative methods and descriptive analysis of secondary data, utilizing conceptual and legal approaches, the research identifies complexities inherent in implementing mandatory vaccination policies during the COVID-19 pandemic. The study reveals diverse viewpoints, conflicting interests, and considerations of pros and cons surrounding policy enforcement and penalties. However,it concludes that the mandatory COVID-19 vaccination policy and its associated sanctions are legitimate from a human rights standpoint. The primary reason to protect others by reducing transmission and the health threat has become a main objective and solid justification behind it. Nonetheless, human rights still do not approve the types of punishment that damage a person's physical health or cause mental or psychological harm and damage or reduce rights that cannot be diminished fundamental rights. It urges the importance of ensuring that any penalties imposed are proportionate, respect human dignity, and do not unjustly curtail rights that are inviolable. Thus, while acknowledging the legitimacy of the mandatory vaccination policy and advocates for careful consideration of human rights principles in the formulation and implementation of penalties associated with it.